Dupilumab: Mechanism of action, clinical, and translational science - Marc R. McCann; Matthew P. Kosloski; Christine Xu; John D. Davis; Mohamed A. Kamal (Wiley, 2024)
Abstract Allergic disease prevalence has increased globally with the subset of type 2 inflammatory diseases playing a substantial role. Type 2 inflammatory diseases may differ in clinical presentation, but they exhibit shared pathophysiology that is targeted by the unique pharmacology of dupilumab. Dupilumab binds to the interleukin (IL)‐4 receptor alpha subunit (IL‐4Rα) that blocks IL‐4 and IL‐13 signaling, two key drivers of type 2 inflammation. Herein, we review the mechanism of action and pharmacology of dupilumab, and the clinical evidence that led to the regulatory approvals of dupilumab for the treatment of numerous type 2 inflammatory diseases: atopic dermatitis, asthma, chronic rhinosinusitis with nasal polyposis, eosinophilic esophagitis, and prurigo nodularis.